CNVs and Chromosomal Aneuploidy in Patients With Early-Onset Schizophrenia and Bipolar Disorder: Genotype-Phenotype Associations - Gregoric Kumperscak, Hojka; Krgovic, Danijela; Drobnic Radobuljac, Maja; Senica, Nina; Zagorac, Andreja; Kokalj Vokac, Nadja (Frontiers in Psychiatry, 2021)
Introduction: Early-onset schizophrenia (EOS) and bipolar disorder (EOB) start before the age of 18 years and have a more severe clinical course, a worse prognosis, and a greater genetic loading compared to the late-onset forms. Copy number variations (CNVs) are an important genetic factor in the etiology of psychiatric disorders. Therefore, this study aimed to analyze CNVs in patients with EOS and EOB and to establish genotype-phenotype relationships for contiguous gene syndromes or genes affected by identified CNVs. Methods: Molecular karyotyping was performed in 45 patients, 38 with EOS and seven with EOB hospitalized between 2010 and 2017. The exclusion criteria were medical or neurological disorders or IQ under 70. Detected CNVs were analyzed according to the standards and guidelines of the American College of Medical Genetics. Result: Molecular karyotyping showed clinically significant CNVs in four patients with EOS (encompassing the PAK2, ADAMTS3, and ADAMTSL1 genes, and the 16p11.2 microduplication syndrome) and in two patients with EOB (encompassing the ARHGAP11B and PRODH genes). In one patient with EOB, a chromosomal aneuploidy 47, XYY was found. Discussion: Our study is the first study of CNVs in EOS and EOB patients in Slovenia. Our findings support the association of the PAK2, ARHGAP11B, and PRODH genes with schizophrenia and/or bipolar disorder. To our knowledge, this is also the first report of a multiplication of the ADAMTSL1 gene and the smallest deletion of the PAK2 gene in a patient with EOS, and one of the few reports of the 47, XYY karyotype in a patient with EOB.